Multifunctional photo-Fenton-active membrane for solar-driven water purification - Lee, Seungheon; Bayarkhuu, Bolormaa; Han, Yejin; Kim, Hye-Won; Jeong, Seongpil; Boo, Chanhee; Byun, Jeehye (Elsevier BV, 2022)
Photo-Fenton-active (PFA) membranes can provide an effective strategy to control various organic pollutants in water purification applications by simultaneously promoting photocatalysis and Fenton reaction. However, the fabrication of PFA membranes with high reactivity and stability remains a significant technical challenge. In this study, we present a simple and versatile technique to fabricate a PFA membrane via in-situ functionalization of polypyrrole (PPy, i.e., photothermal catalyst) and zerovalent iron (ZVI, i.e., photo-Fenton catalyst) nanoparticles. The proposed one-pot two-step protocol involves vapor phase polymerization of pyrrole and subsequent reduction of iron source, which successfully creates a thin catalyst coating on a porous substrate without reducing membrane porosity. The PFA membrane with the dual PPy/ZVI catalyst layer showed high surface wettability, photothermal performance, and photo-Fenton reactivity, thereby enabling effective control of organic contaminants. Specifically, the PFA membrane exhibited near complete removal (>97%) of organic dye molecules in five repeated photo-Fenton-oxidation cycles. We found that robust anchoring of the ZVI within the PPy layer is an important factor for stable photo-Fenton activity of the PFA membrane. The enhanced anti-fouling and self-cleaning properties of the PFA membrane were further demonstrated in oil-emulsion filtration experiments with multiple cycles. Our innovative fabrication approach can serve as a versatile platform for the development of highly reactive and stable PFA membranes for a wide range of solar-driven water treatment applications.